Geographical Crime Displacement : the Robert Taylor Homes and Englewood - Melsness, Dave (My University, 2010)
This project is a case study of the effectiveness of the Chicago Housing Authority's revitalization efforts in creating new lower-crime/livable communities after the demolition of the Robert Taylor Homes in Southern Chicago. Specifically, this project examined the impacts of displacement of population on crime in the 2nd Police District (where the Robert Taylor Homes were) and the 7th Police District comprising the Englewood community to the south. The goal of the project is to see if there is a correlation with the demolition of the complex and crime trends in the 2nd and 7th districts.
Color poster with text, images, and maps.
Keywords: Posters; Crime analysis--Illinois--Chicago; Crime--Illinois--Chicago--Enivronmental aspects; Public housing--Illinois--Chicago--Social aspects; Chicago (Ill.)--Social conditions; Urban renewal--Illinois--Chicago